First use of stereology to quantify the survival of fat autografts - Cuéllar, Eduardo Serna (Image analysis and stereology, 2005)
It is not usual to perform quantitative analyses on surgical materials. Rather, they are evaluated clinically, through qualitative methods, and if quantitation is done, it is on a 2-dimensional basis. In this study, the long-term survival of fat autografts (FAG) in 40 subjects with facial soft tissue defects is quantified. An adipose tissue preparation from the abdomen obtained through liposuction and centrifugation is injected subcutaneously. Approximately 14 months later, the treated area is biopsied. Extensive computer-based histological analyses were performed using the stereological method in order to directly obtain three parameters: volume fraction of adipocytes in the fat tissue (Vv), density (number per volume) of adipocytes in the fat tissue (Nv), and the mean cell volume of adipocytes (VA) in each tissue sample. A set of equations based on these three quantitative parametersis produced for evaluation of the volumetric survival fraction (VSF)of FAG. The presented data evidenced a 66% survival fraction at the l4-month follow-up. In routine practice, it would be sufficient to perform this volumetric analysis on the injected and biopsied fat samples to know whatfraction of the FAG has survived. This is an objective method for quantifying FAG survival and will allow a standardized comparison between different research series and authors.
Keywords: Adipociti; Face; Celica, preživetje; Soft Tissue Injuries; Maščobno tkivo; Adipose Tissue; Adipocytes; Mehko tkivo, poškodbe; Obraz; Transplantation; Presaditev avtologna; Cell Survival; liposukcija; Transplantation, Autologous; stereologija; histologija